SISTEM INFORMASI KEUANGAN PROGRAM PENGEMBANGAN KEWIRAUSAHAAN FTI UAD - Amalya Nurul Khairi; Farid Ma'ruf; Syifa Fitriani; Jefree Fahana (Universitas Ahmad Dahlan, 2020)
PPK FTI provides trainings to 20 tenants consisting of students and alumni of FTI UAD, then selects them into 6 selected tenants who will obtain venture capital in the form of grants, goods, business literature, mentoring, and financial information system training. This training was carried out with the aim of assisting FTI tenants especially in making financial statements. The methods in this activity are divided into three stages, first is the development of PPK FTI UAD financial information system, discussion and practice of filling information systems through offline and online training, and evaluating financial information systems and training through questionnaires on a likert scale. The results shows that most tenants are able to use the information system easily and provide positive feedback with a percentage of the statement of ease of use, features, and access in the range of easy and very easy. PPK financial information system is assessed by tenants according to tenant's needs and greatly saves financial management time. For further development, PPK FTI UAD will continue the activities on basic accounting training, information system improvement, and development of android or iOS applications.